2021
DOI: 10.1159/000511595
|View full text |Cite
|
Sign up to set email alerts
|

Wells Syndrome as a Rare Cause of Unilateral Ptosis

Abstract: We present a case of a woman with a swollen upper eyelid in ptosis, conjunctival nodules, and chemosis present for a couple of weeks. She did not respond to therapy for hordeolum or allergy. A biopsy followed by histopathological examination showed a large infiltration of eosinophilic granulocytes and flame figures, so the diagnosis of Wells syndrome was made. Oral methylprednisolone in high dose was necessary, and tapering was slow because of frequent bouts of relapse. After 3 months, the swelling and hard fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Among these, orbital involvement is one of the most commonly reported findings. 8,9 To our knowledge, we present the first reported case of an orbital silicone implant exposure in a patient with an undiagnosed GPA at presentation. The patient consented to publication and archival of identifiable photographs.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Among these, orbital involvement is one of the most commonly reported findings. 8,9 To our knowledge, we present the first reported case of an orbital silicone implant exposure in a patient with an undiagnosed GPA at presentation. The patient consented to publication and archival of identifiable photographs.…”
Section: Discussionmentioning
confidence: 88%
“…6 Facial lesions secondary to Wells syndrome are exceedingly rare. 4,5,[7][8][9] Of the 8 reported cases in the literature, none were sight-threatening. To the authors' knowledge, this is the first reported case of severe periorbital Wells syndrome causing acute decline in vision requiring urgent intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations